Uncovering the managerial accounting needs of small companies’ entrepreneurs : a contribution to the reduction of enterprise mortality - MAYER, Luiza Teti (2020)
This research aims to uncover the main managerial accounting needs of small enterprises’ entrepreneurs, in order to contribute to the reduction of the mortality rate of their companies. In order to achieve this objective, we developed two connected papers. The first paper investigates the perception of small business owners on the usefulness of managerial and financial accounting information provided by accountants. Data were collected through a survey applied on a sample of 130 small entrepreneurs within the metropolitan region of Recife, a city located at northeast of Brazil. The results show that accountants provide business owners mostly with information and services related to taxes and legal compliance, with little or no participation in the provision of managerial information to enhance performance and control. At the same time, we noticed that there is a demand on the part of the owners and managers to have managerial and financial accounting information. The main limitation of this study is the size of the sample, which may compromise the representativeness and the generalisation of the results. The second paper presents an overview and an analysis of the production costs structure of small enterprises from the state of Pernambuco. Data were collected through a survey applied on a sample of 35 small formal and informal enterprises within the state of Pernambuco. The results show that the companies of our sample do not calculate depreciation costs, as well as the owners do not consider these costs for the pricing strategy. In addition, since most of the companies are informal and are operated from the owner’s home, we also noticed that they do not control electricity costs. One of the limitations of this study is the sample size and the fact that the participants were selected by convenience. Thus, not being possible to generalise the results.